Pemenuhan Hak Istri yang Dipenjara dalam Konsepsi Hukum Islam (Studi Kasus Narapidana Hamil di Lembaga Permasyarakatan Perempuan Kelas II B Sigli) - Meuthia Sari, Cut; Jailani, Jailani; Yahya, Faisal (Tadabbur: Jurnal Peradaban Islam, 2023)
In Islam, husbands have the responsibility to fulfill the rights of their families. However, in the context of convicts, the implementation of these rights can become more complicated due to the limitations imposed by imprisonment. The objectives of this research are: first, to analyze the rights of pregnant wives who are convicted and imprisoned at the Class II B Sigli Women's Correctional Institution in Pidie Subdistrict, Pidie Regency, based on the perspective of Islamic law; and second, to analyze the fulfillment of husbands' obligations towards pregnant convicts at the Class II B Sigli Women's Correctional Institution in Pidie Subdistrict, Pidie Regency. This study adopts an empirical legal research approach (non-doctrinal research). Data were collected through in-depth interviews, observations, and document analysis. The findings of this research resulted in two main outcomes: First, the determination of the obligation to provide financial support for pregnant wives in prison is mandatory due to their pregnancy. Second, the fulfillment of the rights of imprisoned wives by their husbands, as stipulated in the conception of Islamic law, is still not fully achieved. This is due to the husbands' incarceration. Based on these findings, it is recommended to establish regulations regarding the fulfillment of the rights of imprisoned wives by convict husbands. This would involve the cooperation between correctional institutions, authorities, and religious institutions in facilitating easier and more accessible access for convict husbands to fulfill the rights of their imprisoned wives.